Chemical Composition of Mudaffara Cheese Manufactured by Solanum dubium Coat Extract and Chymosin - Harun, Khansa I. I.; Abdalla, Mohamed Osman M.; El Owni, Osman A. O. (Journal of Veterinary Medicine and Animal Production, 2021)
This study was conducted to determine the chemical composition of Mudaffara cheese manufactured by Solanum dubium coat extract and chymosin as coagulant enzymes. Mudaffara cheese was manufactured from warmed (35ºC) raw cow milk to which a starter culture (2% w/w of 1:1 combination of Streptococcus thermophilus and Lactobacillus bulgaricus) was added. In the first treatment, chymosin extract (20 ml /10 L milk) was added, while in the second treatment Solanum dubium coat extract (20 ml / 10 L milk) was added. After coagulation, whey was drained and curd was cut and placed in an incubator at 40ºC for 3 hours, followed by cooking at 75ºC for 5 min. Black cumin (0.5% w/w) was added to the curd and braided into the final form. The curd was preserved in the salted whey (10% w/w) for 24 hours and then the cheese was preserved at 4ºC for 28 days. Chemical analysis was carried out at day 1, 7, 14, 21 and 28. The results showed that all chemical components under study were not significantly affected by the type of coagulant except fat content which was significantly (P<0.001) highest in cheese made with chymosin (17.2%). During the storage period of cheese made by two coagulants, fat content fluctuated showing the highest content (18.46%) at day 21. The protein content gradually decreased till day 21 (19.29%) before increasing towards the end of the period (21.61%). The total solids content steadily increased to 53.61% at day 14 before decreasing at day 21, and then increased at the end (58.45%). The ash content increased to the highest level (15.59%) at day 14, followed by a decrease at day 21 (9.01%) and then increased at day 28 (17.18%). The titratable acidity increased reaching the maximum at day 21 (0.57%) then decreased at the end of the storage period to 0.50%. The fat content of cheese made with chymosin and Solanum dubium coat extract showed a peak at day 21, while protein, total solids and ash contents had the peak at day 28. The acidity fluctuated during the storage period being high at day 7 for cheese made with chymosin and at day 21 for cheese made with Solanum dubium coat extract.